The effects of glipizide on DNA damage and nuclear transport in differentiated 3T3-L1 adipocytes - SÜSLEYİCİ, BELGİN (SPRINGER, 2022)
Background Despite commonly use for treatment of type II diabetes, possible effects of glipizide on nuclear transport and DNA damage in cells are unknown. Since clinical response of glipizide may change with aging, the aim of the study was to investigate the effect of glipizide by comparing mature and senescent adipocytes. Methods and results The effects of glipizide were investigated in 3T3-L1 adipocytes. Effective and lethal doses were determined by real-time monitoring iCELLigence system. Comet assay was performed to determine DNA damage and quantitative PCR was conducted to detect gene expression levels. RAN expressions were found to be up regulated in mature 180 mu M glipizide treated adipocytes compared to control group (p < 0.05); whereas down regulated in senescent 180 mu M glipizide treated adipocytes compared to their control adipocytes (p < 0.05). Olive Tail Moment values were significantly higher in mature 180 mu M glipizide treated adipocytes (MTG) and senescent 180 mu M glipizide treated adipocytes (STG) comparing their untreated controls (p < 0.001 and p < 0.001 respectively). Also class 5 comets that shows severe DNA damage were found to be higher in both MTG and STG groups than their controls (p < 0.001 and p < 0.001, respectively). OTM values were higher in STG than MTG (p < 0.001). Conclusions This is the first study that reports glipizide caused DNA damage increasing with senescence in adipocytes. As a response to glipizide treatment Ran gene expression increased in mature; and decreased in senescent adipocytes. Further studies are needed to reveal the effect of glipizide on DNA and nuclear interactions in molecular level.
Keywords: Glipizide; DNA damage; Nuclear transport; RAN gene; TYPE-2 DIABETES-MELLITUS; COMET ASSAY; RAN GTPASE; CELL-CYCLE; BALANCE; CANCER; PHARMACOKINETICS; GLIMEPIRIDE; SENESCENCE; GLICLAZIDE